2018
DOI: 10.1183/23120541.00147-2017
|View full text |Cite
|
Sign up to set email alerts
|

FeNO-based asthma management results in faster improvement of airway hyperresponsiveness

Abstract: Asthma is characterised by inflammation and respiratory symptoms. Current asthma treatment is based on severity of asthma symptoms only. Exhaled nitric oxide fraction (FeNO) is not recommended by the Global Initiative for Asthma guidelines. The aim was to compare the usefulness of a FeNO guided versus symptom-based treatment in achieving improved asthma control assessed by airway hyperresponsiveness (AHR).80 asthmatic patients were included in a double-blinded, parallel, randomised controlled trial with follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…The largest effect favoring FE NO -based care was in a trial that enrolled patients with markedly uncontrolled asthma at the onset of the study, with this study reporting a significant difference in the ACQ-7 results when using FE NO -based care; however, the differences in the ACQ-7 scores between the groups were fairly small relative to the marked improvement in asthma control identified in both treatment groups (82). The two other studies did not reveal a difference with FE NO -based care, although asthma control was much better at baseline in one study (83); in the other study, the score on the ACQ-7 was used as part of the algorithm to adjust asthma care (84).…”
Section: American Thoracic Society Documentsmentioning
confidence: 93%
See 1 more Smart Citation
“…The largest effect favoring FE NO -based care was in a trial that enrolled patients with markedly uncontrolled asthma at the onset of the study, with this study reporting a significant difference in the ACQ-7 results when using FE NO -based care; however, the differences in the ACQ-7 scores between the groups were fairly small relative to the marked improvement in asthma control identified in both treatment groups (82). The two other studies did not reveal a difference with FE NO -based care, although asthma control was much better at baseline in one study (83); in the other study, the score on the ACQ-7 was used as part of the algorithm to adjust asthma care (84).…”
Section: American Thoracic Society Documentsmentioning
confidence: 93%
“…Three studies evaluated quality of life, but data could not be combined because the studies used slightly different outcome measures. None of the studies showed a significant difference in quality of life with the intervention (83,84,96) (83). No data were identified on the effects on daily activity, exercise, or sports participation.…”
Section: American Thoracic Society Documentsmentioning
confidence: 99%
“…A number of randomized, clinical trials (RCTs) have assessed FeNO as a tool for guiding asthma treatment [ 62 , 63 ]. In an Australian RCT including 220 pregnant, non-smoking asthmatic women, the exacerbation rate was lower in the FeNO-group than in the control group in which the treatment was adjusted according to clinical symptoms, incidence rate ratio 0.47 (0.33–0.76), p = 0.001 [ 62 ].…”
Section: Biomarkers In Asthmamentioning
confidence: 99%
“…In an Australian RCT including 220 pregnant, non-smoking asthmatic women, the exacerbation rate was lower in the FeNO-group than in the control group in which the treatment was adjusted according to clinical symptoms, incidence rate ratio 0.47 (0.33–0.76), p = 0.001 [ 62 ]. A 36-week RCT including 80 asthmatic Danish adults assessed the utility of a FeNO-guided versus symptom-based treatment algorithm [ 63 ]. The decrease in airway hyperresponsiveness (AHR) from week 8 to 24 was significantly different in the FeNO-group compared with the control group, suggesting that the use of FeNO resulted in an earlier lowering of AHR.…”
Section: Biomarkers In Asthmamentioning
confidence: 99%
See 1 more Smart Citation